Oceanographic Data of the 44th Japanese Antarctic Research Expedition from December 2002 to March 2003 - ムネダ, コウジ; オイチ, カズヨシ; Muneda, Koji; Oichi, Kazuyoshi (National Institute of Polar Research, 2006)
P(論文) departmental bulletin paper